MEF2C haploinsufficiency caused by either microdeletion of the 5q14.3 region or mutation is responsible for severe mental retardation with stereotypic movements, epilepsy and/or cerebral malformations. Issue 1 (9th July 2009) - Le Meur, N; Holder-Espinasse, M; Jaillard, S; Goldenberg, A; Joriot, S; Amati-Bonneau, P; Guichet, A; Barth, M; Charollais, A; Journel, H; Auvin, S; Boucher, C; et al.
Abstract : Background: Over the last few years, array-comparative genomic hybridisation (CGH) has considerably improved our ability to detect cryptic unbalanced rearrangements in patients with syndromic mental retardation. Method: Molecular karyotyping of six patients with syndromic mental retardation was carried out using whole-genome oligonucleotide array-CGH. Results: 5q14.3 microdeletions ranging from 216 kb to 8.8 Mb were detected in five unrelated patients with the following phenotypic similarities: severe mental retardation with absent speech, hypotonia and stereotypic movements. Facial dysmorphic features, epilepsy and/or cerebral malformations were also present in most of these patients. The minimal common deleted region of these 5q14 microdeletions encompassed only MEF2C, the gene for a protein known to act in brain as a neurogenesis effector, which regulates excitatory synapse number. In a patient with a similar phenotype, an MEF2C nonsense mutation was subsequently identified. Conclusion: Taken together, these results strongly suggest that haploinsufficiency of MEF2C is responsible for severe mental retardation with stereotypic movements, seizures and/or cerebral malformations.